Trajectoires territoriales d’un nouveau centre extractif mondialisé. L’exemple des Andes argentines septentrionales - Marie Forget (Revue de Géographie Alpine)
Argentina’s mining industry has grown rapidly in recent years, making the sector an essential part of the country’s economy and placing the Andes at the heart of numerous economic, political and social issues. The present article examines the spatial distribution of mining activities and the role attributed to the mountains of northwest Argentina. Exploiting these territories as reservoirs of raw materials was uncontroversial at the beginning of the century; however, this approach is now being contested because it leads to little territorial development. Latin America’s renewed focus on primary industries, involving the extraction and export of unprocessed natural resources, could be viewed as a step back to colonial-style exploitation. As such, it raises questions about North-South relations and the development of mountain territories, which are often peripheral, poor and sparsely populated. Our research examines the territorial-development trajectories of three provinces - San Juan, Catamarca and Jujuy – and analyzes how interactions between governmental and non-governmental actors affect a territory’s approach to constructing and exploiting its resources. Questions about the way in which these interactions shape the development of mountain territories have led to alternative models that take into account the need for territorial development to be built locally.